Repairing and commissioning of an AC motor speed controller for a centrifugal pump - Md. Touhid Nur Rahman; Md. Momin Turzo; Ahammed Masum Billah; Md. Masum Akanda; Md. Rahat Rahman (Journal of Physics and Its Applications, 2019)
A centrifugal pump was installed in 1984 in the Fluid Mechanics Laboratory of Mechanical Engineering Department of Rajshahi University of Engineering & Technology. The motor of the centrifugal pump was dc motor and was not working. It could not be commissioned for a long time because of the damaged speed controller. The main shaft (rotor) was also jammed. In this project work, the dc motor was tried to repair. But it could not be run because the specification of the motor and the operating manual was not available. To complete the project successfully, the dc motor was replaced by an ac induction motor. After replacing the motor, the speed of the new motor was controlled by a variable frequency drive (VFD). Using this device, the speed was controlled from 600 rpm to 3000 rpm smoothly. After the replacement, the testing of the centrifugal pump was successfully performed and the motor was controlled in various speeds. Experiment on the performance test of the centrifugal pump was carried out satisfactorily running the pump in various speeds operated by the VFD.